The Effect of Brand Image, Product Quality, and Price on Repurchase Intention on Janji Jiwa - Muliawan, Adi; Shiratina , Aldina (ARE Publisher, 2024)
The high coffee consumption phenomenon in Indonesia, especially Kopi Janji Jiwa, encourages this research to understand the factors that influence consumer Repurchase Intention. This study aims to analyze the influence of Brand Image, Product Quality, and Price on Repurchase Intention on Kopi Janji Jiwa. The population in this study is someone who has made at least 2 purchase transactions on Kopi Janji Jiwa products in the West Jakarta area. As many as 150 respondents with an age range of 18-55 years were selected as research samples using the Hair formula. Data was collected through a survey method using a Google form questionnaire. The sampling technique and method quantitative and used purposive sampling. The data was analyzed using the Structural Equation Model (SEM) with the SmartPLS analysis tool. This study proves that Brand Image has a Positive and significant effect on Repurchase Intention, Product Quality has a Positive and significant effect on Repurchase Intention, and Price Quality has a Positive and significant effect on Repurchase Intention.